Auditor reporting to bank regulators: effective regulation or regulatory overreach? - Amel-Zadeh, A; Barth, ME (Elsevier, 2021)
We discuss “Economic Consequences of Mandatory Auditor Reporting to Bank Regulators” by Balakrishnan, De George, Ertan, and Scobie (BDES, in this issue). BDES concludes that a key benefit of mandatory auditor reporting to bank regulators is reduced bank risk, and its costs include reduced profitability from less overall and less risky lending, and higher audit costs. BDES also provides evidence on the channels through which mandatory auditor reporting links to reduced bank risk. We scrutinize BDES's analyses and inferences and suggest additional analyses to improve and deepen them. Most notably, we caution that effective bank regulation entails reducing risk for riskier banks; risk reduction for safer banks suggests regulatory overreach. Our evidence is more indicative of regulatory overreach. Thus, although BDES is an important step forward in understanding the role auditors can and do play in improving information available to key decision-makers other than through auditor reports on financial statements and internal controls, a comprehensive assessment of whether the benefits of mandatory auditor reporting to bank regulators exceed its costs is left for future research. Such an assessment is necessary before concluding whether mandatory auditor reporting leads to more effective bank regulation or regulatory overreach.